Exploring the social context of smoking behaviours: insights from stop-smoking advisors in deprived communities in Northwest of England UK - Mzwandile Mabhala; Winifred Adaobi Esealuka; Asmait Yohannes; Amanda Nkolika Nwufo; Lahja Paulus; Meron Tefera; June Keeling (BMC Public Health)
Abstract Background Successive UK governments have introduced measures to enhance access to stop-smoking services. However, these efforts have primarily focused on restricting access to tobacco products and promoting individual behaviour changes, overlooking the social conditions that contribute to smoking behaviours. While promoting individual behaviour changes can be beneficial, lasting change requires collective action and structural reforms. This research examines the limitations of individual-focused stop-smoking interventions in deprived communities. It emphasises the significance of adopting a comprehensive smoking cessation strategy that take into account the broader socioeconomic determinants. These findings are crucial for understanding the complexities of smoking cessation in deprived communities. Methods This study uses interpretive phenomenology and socioeconomic determinants theories to analyse the experiences of stop-smoking advisors in promoting smoking cessation initiatives within a disadvantaged neighbourhood in northwest England. In this study, stop-smoking advisors are practitioners trained to provide support and guidance through various methods, such as one-on-one counselling, group meetings and workshops. The research took place between March and July 2019 at a local authority-owned lifestyle centre in the most deprived community in northwest England. Results The analysis identified four overarching themes: 1) Developing a skilled, confident, and culturally competent stop-smoking advice team, 2) Understanding other complex social, mental, and physical health issues, 3) Bringing the stop-smoking programme to those who need it the most, 4) Adapting the service to meet the user’s needs. Conclusions The behaviour-oriented interventions have resulted in a disproportionate decrease in smoking rates, with a more rapid decline in the least deprived areas compared to the deprived ones. The inverse care law theory provided a compelling framework for understanding these differences. It emphasised equal consideration of behavioural and structural interventions in addressing smoking habits in deprived neighbourhoods, highlighting the impact of socioeconomic factors and the limitations of individual behaviour-focused stop-smoking interventions.